Decreasing mortality after femoral neck fracture treated with bipolar hemiarthroplasty during the last twenty years - Schneppendahl, Johannes; Grassmann, Jan-Peter; Petrov, Vanco; Boettner, Friedrich; Koerbl, Birthe; Hakimi, Mohssen; Windolf, Joachim; Wild, Michael; Betsch, Marcel (International Orthopaedics, 2012)
Purpose: The aim of our study was to investigate trends over time in the mortality of elderly patients after femoral neck fractures treated with bipolar hemiarthroplasty. Methods: Altogether 487 cases of femoral neck fracture treated with bipolar hemiarthroplasty were observed during a 20-year period. Mortality rates were calculated for five years postoperatively. To account for the age distribution of the study population standardised mortality ratios (SMR) with respect to the age-specific mortality of the German population were determined and compared. Additional changes of the SMRs over time and the influence of the time delay before surgery on long-term mortality were evaluated. Results: Femoral neck fractures treated with bipolar hemiendoprosthesis have a significant impact on mortality. Postoperative mortality is increased in patients of all age groups, but the effect diminishes in higher age groups. The influence on mortality was significantly greater for men than for women. The SMR has decreased from 3.52 before 1995 to 1.2 after 2006. Since 2006 there is no longer an increase in mortality after surgical treatment of a femoral neck fracture compared to general German population of the same age. Conclusion: Femoral neck fractures treated with bipolar hemiendoprosthesis result in a significantly increased mortality, however in our population this impact has significantly decreased over time. The effect on mortality is less in women and higher age groups than in men and younger patients. No influence of the time between accident and surgery on mortality could be detected. © 2012 Springer-Verlag.
CRIS-Team Scopus Importer:2022-07-20